Prediction of Failed Fibrinolytic Using Scoring System in ST Elevation Myocardial Infarction Patients - Satria Mahendra; Budi Yuli Setianto; Hariadi Hariawan (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2016)
Background: ST elevation myocardial infarction (STEMI) is the most common acute coronary syndrome in adults, and requiring immediate reperfusion. Primary percutaneous coronary intervention (PCI) is the main reperfusion therapy, but because of many limitations, fibrinolytic is often chosen. Fibrinolytic have high failure risk, so it is important to be able to predict whether this therapy will fail or not. This research aim to create a scoring system to predict failed fibrinolytic in STEMI patients. Methods: This is retrospective cohort study using medical records data from Dr. Sardjito General Hospital in Yogyakarta, recorded in June 2014-December 2015. The population was STEMI patients that reperfused with streptokinase regiment. Determination of failed fibrinolytic was using the difference in the ST segment elevation of the pre and post fibrinolytic electrocardiogram (ECG). The clinical variables of subjects were recorded. The statistical analysis was done and scoring system was constructed. Results: A total of 105 patients with mean age of 57.82±9.59 years were included in this study. Subjects with failed fibrinolytic was 53 patients (50.5%). Several variables were independently associated with failed fibrinolytis, i.e. the onset of ≥ 6 hours, hyperglycemia, and the location of anterior infarction (OR = 11.3, p = 0.000; OR = 6.11, p = 0.003 and OR = 10.5, p = 0.001, respectively). After scoring system was constructed, it was found that score ≥ 2 predict failed fibinolytic, with 53% sensitivity and 94% specificity. Conclusions : Scoring system consisting of onset ≥ 6 hours, hyperglycemia in arrival, and anterior infarct location, can be used to predict failed fibrinolytic in STEMI patients using streptokinase with 53% sensitivity and 94% specificity. Keywords: failed fibrinolytic scoring; fibrinolytic; STEMI; streptokinase